Metamodelling technique for the efficient design optimisation of metasurfaces. Issue 14 (1st July 2016) - Ferranti, F.; De Marcellis, A.; Janneh, M.; Palange, E.; Antonini, G.
Abstract : A metamodelling technique for the efficient design optimisation of the electromagnetic response of metasurfaces is proposed. Metamodels are built starting from data samples of design performance parameters properly extracted from a few electromagnetic simulations using a system identification approach. The metamodels are then used to optimise the metasurface electromagnetic response with respect to some design specifications. Numerical results validate the efficiency and accuracy of the proposed metamodelling technique.